2004
DOI: 10.1007/s00705-004-0440-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular criteria for genus and species discrimination within the family Potyviridae

Abstract: A phylogenetic analysis of the optimised nucleotide (nt) alignment of the entire ORFs of a representative of each fully-sequenced species in the family Potyviridae provided strong support for several subgroups within the genus Potyvirus. A complete set of two-way comparisons was done between the sequences for the entire ORF and for each gene amongst all the 187 complete sequences from the family. Most species had 50-55% nt identity to other members of their genus in their ORFs but there were significant groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
256
2
20

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(313 citation statements)
references
References 29 publications
20
256
2
20
Order By: Relevance
“…The 86-87 % sequence identities of isolates under study with other BYMV strains reported all over the world and in accordance with the species demarcation criteria and identification guidelines for potyviruses [1] suggested the virus isolates of V. faba under study as two isolates of BYMV.…”
supporting
confidence: 63%
“…The 86-87 % sequence identities of isolates under study with other BYMV strains reported all over the world and in accordance with the species demarcation criteria and identification guidelines for potyviruses [1] suggested the virus isolates of V. faba under study as two isolates of BYMV.…”
supporting
confidence: 63%
“…Our observations strengthen the view point of Adams et al [1] regarding the utility of CP gene in virus strain identification. Analysis of CP and CI (Cylindrical inclusion) region of potyvirus genome suggested that CI region provides better insight as it represents the reflection of complete ORF in the absence of full genome and has been regarded as the most accurate region for species identification [1]. However, to establish the identity of the newly designated strains, NL-1n and NL-7n needs confirmation by complete genome characterization.…”
Section: Resultssupporting
confidence: 90%
“…As proteases P1 e HC-Pro autoclivam-se e a NIa está envolvida em seu próprio processo de clivagem em cis e em seis clivagens adicionais em trans, no total de oito a dez peptídeos maduros (Adams et al, 2005; Chung et al, 2008;Azad et al, 2014) (Tabela 2).…”
Section: Família Luteoviridaeunclassified
“…partir de estudos anteriores (Adams et al 2005;2015) foram preditas dez proteínas maduras (P1, HC-Pro, P3, 6k1, CI, 6k2, NIa-VPg, NIa-pro, NIb e CP) produzidas a partir da poliproteína. A análise da poliproteína, na junção entre as proteínas, estão previstas na Tabela 7.…”
Section: Prsvunclassified
See 1 more Smart Citation